Psychological interventions for children and young people affected by armed conflict or political violence: a systematic literature review. Issue 2 (July 2016) - O'Sullivan, Clodagh; Bosqui, Tania; Shannon, Ciaran
Abstract : Youths exposed to armed conflict have a higher prevalence of mental health and psychosocial difficulties. Diverse interventions exist that aim to ameliorate the effect of armed conflict on the psychological and psychosocial wellbeing of conflict affected youths. However, the evidence base for the effectiveness of these interventions is limited. Using standard review methodology, this review aims to address the effectiveness of psychological interventions employed among this population. The search was performed across four databases and grey literature. Article quality was assessed using the Downs and Black Quality Checklist (1998). Where possible, studies were subjected to meta-analyses. The remaining studies were included in a narrative synthesis. Eight studies concerned non clinical populations, while nine concerned clinical populations. Review findings conclude that Group Trauma Focused–Cognitive Behavioural Therapy is effective for reducing symptoms of posttraumatic stress disorder, anxiety, depression and improving prosocial behaviour among clinical cohorts. The evidence does not suggest that interventions aimed at non clinical groups within this population are effective. Despite high quality studies, further robust trials are required to strengthen the evidence base, as a lack of replication has resulted in a limited evidence base to inform practice.